Targeted crop pollination by training honey bees: advances and perspectives - Farina, Walter M.; Arenas, Andrés; Estravis-Barcala, M. Cecilia; Palottini, Florencia (Frontiers in Bee Science, 2023)
As pollinator-dependent crops continue to expand globally, management strategies are needed to meet the current demand for pollination services. Improving the efficiency of pollinators depends on knowledge about crop plant biology as well as pollinator behavior. In this sense, we will review the scope and challenges of implementing a targeted pollination strategy based on the behavioral individual and social plasticity of the honey bee Apis mellifera. Here we summarize current knowledge on the bees´ ability to perceive, learn and generalize floral odors, the bias of their foraging preferences after in-hive experiences and the transfer of food source information within the social context of the colony, all aspects that impact on foraging decisions and can be used to direct pollinators to target crops. We focused on describing how key olfactory cues that mimic crop floral scents are acquired in the hive and propagate among colony mates to guide foraging to specific crops. Knowledge gaps, including volatiles variability between flowers of the same or different crop varieties, alternative managed pollinators, and potential impact on food industry are discussed.